Demographic factors and marital status: Do they really influence the quality of nursing work life? - Kurniasih, Yuni; Melinda, Dina; Ramdhani, Wawan Febri (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Quality of Nursing Work Life (QNWL) is a crucial factor influencing nurses' well-being and performance. Although demographic factors, including marital status, are often considered determinants of QNWL, research findings on their impact remain inconsistent. Purpose: To assess whether demographic factors and marital status, have a significant impact on the Quality of Nursing Work Life (QNWL) among nurses. Method: A cross-sectional design involving 72 nurses working in inpatient care units. Data were collected using a validated QNWL questionnaire and analyzed using Spearman’s rank correlation test to evaluate the relationship between marital status and QNWL. Results: The majority of nurses reported their QNWL as "Good" (93.1%), while a small proportion rated it as "Excellent" (6.9%). Spearman’s correlation analysis indicated no significant relationship between marital status and QNWL (r = 0.152, p = 0.203, p > 0.05). This suggests that marital status is not a determining factor in nurses' quality of work life. Conclusion: Marital status does not significantly affect QNWL. Other factors, such as work environment, workload, shift system, and organizational support, are likely to have a greater influence. Further research is recommended to explore additional factors to develop more targeted strategies for improving nurses' quality of work life.